Synthesis of Silver Nanorods Using Lamellar Liquid Crystal of Protic Ionic Liquids - Hong Li*, Qiu; Li, Peng; Zhang, Xiaolong (Asian Journal of Chemistry, 2013)
Silver nanorods are prepared by reduction of silver nitrate in lamellar lyotropic liquid crystal mainly made of poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) block copolymers (P123) and protic ionic liquids (PILs) EAN. Liquid crystal was characterized by polarized optical microscope and small-angle X-ray scattering measurements. Scaning electron microscopy (SEM) and UV-visible spectroscopy show the formation of nanorods. The effects of the concentrations of silver nitrate on the formation of the nano-products are discussed. The average diameter of silver nanorods with 30-50 nm can be observed and the length of nanorods is about 500 nm. The result indicates that the lamellar lyotropic liquid plays an important role for the consequent growth of nanorods by providing an ordered reaction medium and a limited growth space.